Verb Doubling and Dummy Verb Gap Avoidance Strategies in Verbal Fronting - Hein, Johannes (Linguistische Arbeiten ;, 2020)
This monograph provides the first cross-linguistic study of repair strategies in verbal fronting, verb doubling and do-support, addressing both typological properties and theoretical aspects. First, it brings together data hitherto scattered across the empirical and theoretical literature and adds newly collected data from two African languages. For each of the 47 languages, the properties of verbal fronting are documented in detail. Based on this sample, the empirical part establishes two novel typological generalizations regarding the interaction between the size of the fronted category and the type of repair strategy used. The first of these identifies a systematic typological gap: No language that allows both verb and verb phrase fronting has do-support with the former and verb doubling with the latter. In the theoretical part, it is shown that previous theories of verb doubling/do-support are unable to account for both generalizations. A new approach within the Copy Theory of the Minimalist Framework is developed, that rests on the interaction of head movement, copy deletion, and the properties of different movement types. The book thus provides the first comprehensive empirical and theoretical overview of repair patterns in verbal fronting.